Fuel consumption and CO2 emissions of passenger cars over the New Worldwide Harmonized Test Protocol. (1st October 2016) - Tsokolis, D.; Tsiakmakis, S.; Dimaratos, A.; Fontaras, G.; Pistikopoulos, P.; Ciuffo, B.; Samaras, Z.
Highlights: CO2 measurements for 12 gasoline and 8 diesel vehicles over the NEDC and WLTP-H. Discussion on the differences between the test protocols of WLTP and NEDC. Analysis of the cold start effect over NEDC and WLTP-H. Quantification of the ΔCO2 between WLTP-H and NEDC for a small gasoline and a medium diesel vehicle. Abstract: In 2014 the United Nations Economic Commission for Europe (UNECE) adopted the global technical regulation No. 15 concerning the Worldwide harmonized Light duty Test Procedure (WLTP). Having significantly contributed to its development, the European Commission is now aiming at introducing the new test procedure in the European type-approval legislation for light duty vehicles in order to replace the New European Driving Cycle (NEDC) as the certification test. The current paper aims to assess the effect of WLTP introduction on the reported CO2 emissions from passenger cars presently measured under the New European Driving Cycle and the corresponding test protocol. The most important differences between the two testing procedures, apart from the kinematic characteristics of the respective driving cycles, is the determination of the vehicle inertia and driving resistance, the gear shifting sequence, the soak and test temperature and the post-test charge balance correction applied to WLTP. In order to quantify and analyze the effect of these differences in the end value of CO2 emissions, WLTP and NEDC CO2 emission measurements were performed on 20 vehicles, covering almost the whole European market. WLTP CO2 values range from 125.5 to 217.9 g/km, NEDC values range from 105.4 to 213.2 g/km and the ΔCO2 between WLTP and NEDC ranges from 4.7 to 29.2 g/km for the given vehicle sample. The average cold start effect over WLTP was found 6.1 g/km, while for NEDC it was found 12.3 g/km. For a small gasoline and a medium sized diesel passenger car, the different inertia mass and driving resistance is responsible 63% and 81% of the observed ΔCO2 between these two driving cycles respectively, whereas the other parameters (driving profile, gear shifting, test temperature) account for the remaining 37% and 19%.